REKONSTRUKSI KONSEP AURAT (Analisis Pemikiran Syahrur) - Khoiri, Muhammad Alim (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2015)
Dr. Ir. Muhammad Shahrur, a syrians controversial liberal thinkers dubbed as "Immanuel Kant" of the Arab world and the "Martin Luther" of the Islamic world is one of the intellectuals who have a critical awareness to make updates to the understanding of religion. One of his idea is a buzz about the genitalia concept. Shahrur stated that the issue of genitalia is merely historical problem that is not free from various influences and manipulations. It was not a pure ubudiyah problem. So the genitalia concept is relative, according to the social and cultural conditions surrounding the boundary but still within the frame of the God.Shahrur’s concept would offer very appropriate to be used as one blade analysis in addressing the phenomenon of 'jilboobs'. So far, classical approach used by many people in seeing the phenomenon of 'jilboobs' seem extreme. Of course, this method is not effective, because all it takes is a persuasive approach. So in this case examines the Shahrur’s concept could be an alternative solution.Keywords: Shahrur, Genitalia, Reconstruction